Enhanced efficacy of formoterol-montelukast salt in relieving asthma features and in preserving β2-agonists rescue therapy. (December 2022) - Cerqua, Ida; Granato, Elisabetta; Petti, Antonio; Pavese, Rocco; Costa, Soraia Kátia Pereira; Feitosa, Karla Barroso; Soares, Antonio Garcia; Muscara, Marcelo; Camerlingo, Rosa; Rea, Giuseppina; Fiorino, Ferdinando; Santagada, Vincenzo; et al.
Abstract: Adrenergic β2-agonists represent a mainstay in asthma management. Their chronic use has been associated with decreased bronchoprotection and rebound hyperresponsiveness. Here we investigate on the possible therapeutic advantage of a pharmacological association of β2-agonists with montelukast, a highly selective leukotriene receptor antagonist, in modulating bronchial reactivity and controlling asthma features. The study has been conducted in vitro and in vivo and also takes advantage of the synthesis of a salt that gave us the possibility to simultaneously administer in vivo formoterol and montelukast (MFS). In vitro studies demonstrate that montelukast (1) preserves β2-agonist response in isolated bronchi by preventing homologous β2-adrenoceptor desensitization; (2) reduces desensitization by modulating β2-receptor translocation in bronchial epithelial cells. In vivo studies demonstrate that sensitized mice receiving formoterol or montelukast display a significant reduction in airway hyperresponsiveness, but the β2-agonist relaxing response is still impaired. Allergen challenge causes β2 heterologous desensitization that is further increased by treatment in vivo with formoterol. Conversely MFS not only inhibits airway hyperresponsiveness but it rescues the β2-agonist response. Histological analysis confirms the functional data, demonstrating an enhanced therapeutic efficiency of MSF in controlling also pulmonary metaplasia and lung inflammation. MFS is efficacious also when sensitized mice received the drug by local administration. In conclusion, the data obtained evidenced a therapeutic advantage in the association of β2-agonists with montelukast in the control of asthma-like features and a better rescue bronchodilation response to β2-agonists. Graphical Abstract: ga1